Research in Plastic Design of Multi-story Frames - Driscoll, Jr.; Beedle, Lynn S. (Engineering Journal, 1964)
The eighth National Engineering Conference, held at Lehigh University in 1956, was devoted in its entirety to the subject of plastic design. At that time there were no plastically designed structures in the United States, or at least there were none that were a matter of record. Undoubtedly there must have been a number of structures designed on the basis of what has been described as a "plastic excuse for an elastic design"; and of course the provision included in the AISCSpecification in 1945 that permitted a 20 percent increase of stress at points of interior support could only be justified on the basis of the same concepts that led to the current plastic design techniques. The purpose of these remarks is to review briefly the advances made since 1956 and to describe in some detail the research being conducted at Lehigh University on the plastic design of multi-story building frames. The latter discussion is divided into two parts: braced frames and unbraced frames. In addition the results of recent pilot tests on a three-story structure are presented.